Influence of Market Mix Strategy (Marketing Mix) Towards the Increase in the Number of New Students of SDIT Ar-Treatise Seteluk - Saprianto Saprianto; Ahmad Yamin; Dedi Supriadi (Journal of Social Research, 2022)
Background: Education is one of the efforts made to improve the quality of human resources which in essence helps, humans, to be smart, smart and smart. The school is one provides institutions that provide education and learning for children who are not only normal but also have special needs. Objective: To explain the effect of the educational marketing mix at SDIT Ar-Risalah on the increase in the number of students. Method: Based on the title proposed by the researcher, namely "The Effect of Educational Marketing Mix on the Improvement of Students at SDIT Ar-Risalah Seteluk", this study uses quantification research, which is a process where research data in the form of numbers, then analyzed using statistical tests. Results: Education services at SDI Surya Buana and MIN Malang 2 prioritize efforts to fulfill customer satisfaction. Marketing strategies in improving the image are carried out, namely direct, indirect, differentiation, and financing. The impact of marketing strategies and their implications on imaging at SDI Surya Buana and MIN Malang 2. Conclusion: From the results of data analysis and discussion, the author can conclude that: Marketing Mix has a positive and significant effect on the Increase of Students at SDIT Ar-Risalah Seteluk.